Validity of pecking order and trade-off theories in explaining capital structure of listed firms in South Africa - Tunde, Matemilola Bolaji (2012)
Theoretical and empirical debates on how firms finance themselves remain inconclusive. Pecking order and trade-off theory of capital structure emerge as the main theories of capital structure that explains how firms finance themselves in real world. However, static model specifications are mostly used to test these theories. The study analyses the validity of pecking order theory and trade-off theory of capital structure on South Africa listed firms using dynamic panel model specifications. It uses panel regression and generalized method of moment estimation technique to determine the relation between profit and long-term debt, as well as the relation between profit and total debt. Moreover, panel regression and generalized method of moment is used to determine the relation between fixed assets and long-term debt as well as the relation between fixed assets and total debt. The results of pecking order theory show that profit has significance negative relation with long-term debt. Similarly, profit has significant negative relation with total debt. The results of the trade-off theory show that fixed asset has significant and positive relation with long term debt. Similarly, fixed asset has significant and positive relation with total debt. In addition, the coefficient of lagged dependent variable indicates that firms’ adjust back to their target debt level. In general, the results support the pecking order theory and trade-off theory and they are consistent with empirical findings in developed countries. The evidence of pecking order theory implies need to further develop the capital market in order to minimize information asymmetry costs associated with raising external finance. Furthermore, the evidence of trade-off theory implies that fixed assets are required as collateral to obtain long-term capital needed to finance profitable investment opportunities in South Africa. Moreover, the trade-off theory implies that South African firms have target debt level and they make effort to adjust to their target debt level. The study contributes to empirical research on capital structure in Africa. In addition, the study uses better estimation technique which is Generalized Method of Moments that control for unobservable firm-specific effects and endogenous problem, and better able to give consistent estimators that are robust to heteroskedasticity and serial correlation.